NO’ANAVIY KINOA (Chenopodium quinoa Willd.) EKININING DUNYO BO‘YICHA OZIQ-OVQAT SANOATIDAGI TUTGAN O’RNI. (AGROINNOVATSIYА, 2024)
In this article, the composition, biological characteristics, role of the non-traditional quinoa ( Chenopodium quinoa Willd.) crop, its role in the food industry, the level of demand for the cultivation and consumption of this type of crop by the countries of the world, the recognition of this crop by the UN The importance of the plant and its resistance to drought and salinity in different soil conditions are explained.